Harnessing proteins for engineered living materials. Issue 1 (February 2021) - Xu, Lianjie; Wang, Xinyu; Sun, Fei; Cao, Yi; Zhong, Chao; Zhang, Wen-Bin
Highlights: Engineered living materials (ELMs) are materials with living features. Proteins play an essential role in current ELM designs. Future development of ELMs would benefit from a systems perspective beyond components. Abstract: Engineered living materials (ELMs) have drawn intense interest from both academia and industry in recent years. The essence of ELMs is the use of living cells to produce molecular building blocks, direct their hierarchical organization, and convert life into functional materials. By doing so, it confers living features on materials, including self-organization, self-maintaining, adaptability and evolvability. As the workhorse of life, proteins play an essential role in current ELM designs. To harness proteins for applications in ELMs, protein engineering is usually required to tailor their assembly, chemistry, functions, and their interactions with abiotic materials. In this review, we discuss the roles of proteins in ELMs and summarize the applications of protein engineering in developing molecular tools toward the creation of advanced ELMs with novel properties. Inspired by systems chemistry, we emphasize that future development of ELMs would benefit from a systems perspective by integrating a rich and versatile interaction network comprising multiple functional components such as genes, RNAs, proteins, and even many other abiotic components.